2018
DOI: 10.1038/s41598-018-32324-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profile of Blood Monocytes is Altered in HTLV-1 Infected Patients: Implications for HAM/TSP Disease

Abstract: Human T-cell lymphotropic virus type-1 (HTLV-1) is the etiological agent of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). The endothelial breakdown and migration of leukocytes, including monocytes, to the spinal cord are involved in HAM/TSP development. Monocytes from HTLV-1-infected individuals exhibit important functional differences when compared to cells from uninfected donors. Using proteomic shot gun strategy, performed by nanoACQUITY-UPLC system, we analyzed monocytes isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Enose-Akahata et al (2012) observed the presence of phagocytes expressing high levels of HLA-DR and CX3CR1 in spinal cord injuries of individuals with HAM/TSP [21]. Using proteomic analysis, our group revealed important changes in the expression of cytoskeletal proteins in monocytes of HTLV-1 carriers, demonstrating an increase in proteins associated with adhesion and migration phenomena, such as gelsolin [17].…”
Section: Introductionmentioning
confidence: 72%
“…Enose-Akahata et al (2012) observed the presence of phagocytes expressing high levels of HLA-DR and CX3CR1 in spinal cord injuries of individuals with HAM/TSP [21]. Using proteomic analysis, our group revealed important changes in the expression of cytoskeletal proteins in monocytes of HTLV-1 carriers, demonstrating an increase in proteins associated with adhesion and migration phenomena, such as gelsolin [17].…”
Section: Introductionmentioning
confidence: 72%
“…Heat shock proteins and cytoskeleton proteins were found to be upregulated, while canonical histones were downregulated in monocytes of HTLV-1-infected individuals. 9 However, there is no study available in the literature using the same markers as we used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HTLV-1 infection leads to changes in the levels of some proteins. 1,9,10 Therefore, this study was conducted to evaluate some biomarkers (haematological, biochemical, and serological) in an HTLV-1-positive donor, which could be used for early HTLV-1 detection.…”
Section: 8mentioning
confidence: 99%
“…Thus, the regulation of HAX‐1 stability may be one of the pathways used by HBZ to block apoptosis. Another study demonstrated that monocytes isolated from HAM/TSP patients exhibit higher ability for adhesion and transmigration via endothelium than those isolated from asymptomatic carriers and uninfected individuals (Echevarria‐Lima et al, 2018). It has also been shown that HBZ resides exclusively in the cytoplasm of infected‐cells in asymptomatic carriers and HAM/TSP patients (Forlani et al, 2019).…”
Section: Discussionmentioning
confidence: 99%